Earnings-related severance pay - Laszlo Goerke (Institute for the Study of Labor (IZA), 2006)
In an efficiency wage economy, lump-sum severance pay from which shirkers can be excluded raises employment. However, severance payments are usually related to wages. It is shown that earnings-related, mandated severance pay will have ambiguous employment effects if effort can be varied continuously. A substitution of the earnings-related for the lump-sum component reduces employment. Thus, the prevalent form of severance payments in OECD countries might have less advantageous employment effects than previously conjectured.
Keywords: J32; J41; J65; 330; earnings relationship; efficiency wages; employment; severance pay; Effizienzlohn; Abfindung; Beschäftigung; Theorie